2017
DOI: 10.4172/2161-0444.1000430
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones and Other Compounds from the Roots of Iris marsica I. Ricci E Colas. Collected from Majella National Park, Italy

Abstract: In this study, a phytochemical analysis was performed, for the first time, on Iris marsica I. Ricci e Colas. In particular, the attention was focused on the constituents of the roots. Twenty-one compounds were isolated by column chromatography and were analyzed/identified by NMR spectroscopy and mass spectrometry. They all own chemotaxonomic, ethno-pharmacological and nutraceutical relevance which allowed us to provide a phytochemical rationale, for the correct botanical classification of this species, for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Seven isoflavones (15, 19, 24, 31, 32, 34, 36) and irisxanthone (11) could be isolated and fully structure elucidated by Furthermore, phytochemical analysis of native populations of I. adriatica could also have possible taxonomic implications on different classification levels. Namely, chemical constituents are genetically controlled traits that are sometimes considered to have advantages over morphological ones in systematic research (Harborne and Turner 1984), and taxonomically useful phenolic variations have been established in the family Iridaceae (Harborne and Williams 2000), genus Iris (Wang et al 2010), and especially in some other taxa of the subgenus Iris (Williams et al 1997(Williams et al , 2000Rusak et al 2005;Venditti et al 2017;Abdel-Mageed et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Seven isoflavones (15, 19, 24, 31, 32, 34, 36) and irisxanthone (11) could be isolated and fully structure elucidated by Furthermore, phytochemical analysis of native populations of I. adriatica could also have possible taxonomic implications on different classification levels. Namely, chemical constituents are genetically controlled traits that are sometimes considered to have advantages over morphological ones in systematic research (Harborne and Turner 1984), and taxonomically useful phenolic variations have been established in the family Iridaceae (Harborne and Williams 2000), genus Iris (Wang et al 2010), and especially in some other taxa of the subgenus Iris (Williams et al 1997(Williams et al , 2000Rusak et al 2005;Venditti et al 2017;Abdel-Mageed et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, six compounds have been evidenced in two organs, whereas all the remaining ones only in one organ. For what concerns the amounts of them, it was observed that for acetyl-isocupressic acid (1), sandaracopimaric acid (3) and glucose (9), the relative percentages were much higher in the half-matured female cones. On the other hand, the relative percentage of wollemol (4) is higher in the male cones and the relative percentage of shikimic acid (7) is higher in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…7"-O-methyl-agathisflavone (5) shows antiviral properties against HSV-1 and HSV-2 [23], as well as inhibiting properties on DNA topoisomerases II-α and K562 leukemia cells [24]. Shikimic acid (7) presents antiviral, anti-inflammatory, antioxidant, anticoagulant and neuroprotective effects [9]. Quinic acid (8) owns antiviral and astringent properties [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this chromatographic separation, twelve compounds were isolated and identified after comparison with data reported in literature: pheophytin a ( 1 ) as almost pure compound from the assembly of fractions 1 – 13 for the total weight of 99.8 mg; kickxioside ( 6 ) and 5‐ O ‐menthiafolioylkickxioside ( 7 ) as a mixture in ratio 3:1 from the assembly of fractions 14 – 19 for the total weight of 111.9 mg; linarioloside ( 8 ) together with linariin ( 2 ) and kickxioside ( 6 ) as a mixture in ratio 1:3:4 from fraction 33 for the total weight of 15.9 mg; antirrhinoside ( 11 ) as almost pure compound from the assembly of fractions 55 – 92 for the weight of 55.5 mg; 6‐ O ‐isovaleroylantirrhinoside ( 12 ), mussaenosidic acid ( 10 ), mannitol ( 5 ), and 6,7‐dihydrofoliamenthoic acid methyl ester ( 4 ) as a mixture in ratio (4:2:4:1) from the assembly of fractions 93 – 133 for the total weight of 77.1 mg; 5‐ O ‐glucosylantirrhinoside ( 13 ), mannitol ( 5 ), and sucrose ( 14 ) as a mixture in ratio (1:4:2) from the column wash in methanol for the total weight of 33.9 mg.…”
Section: Methodsmentioning
confidence: 99%